THE INFLUENCE OF TEACHER FEEDBACK ON STUDENT PERFORMANCE IN ENGLISH LEARNING ("Conference on Universal Science Research 2023", 2024)
This article explores the impact of various teacher feedback strategies on student performance in English language learning. It examines different types of feedback, their timing, and the balance between positive and constructive feedback.